New threats on the way of overcoming tobacco smoking in adolescents in Ukraine - N.S. Polka; O.V. Dobrianska (Zaslavsky O.Yu., 2019)
Background. Tobacco smoking is a manageable risk factor, which negative influence can be minimized with a total cessation of smoking. Reducing the prevalence of smoking by 30 % among people over 15 years of age until 2025 is a strategic purpose of the World Health Organization (WHO). Compliance with the WHO Framework Convention on Tobacco in all countries is one of the main goals of the United Nations Sustainable Development Agenda. The purpose was to determine the peculiarities of the prevalence of tobacco smoking in adolescents, to assess the levels of prevalence of new types of tobacco products among them. Materials and methods. In 2017, the third wave of the Global Youth Tobacco Survey (GYTS) took place in Ukraine. Totally, 4,065 7th-9th graders were surveyed (among them 3,040 children aged 13-15 years have been questioning). Survey response rate was 81.6 %. Results. We determined the positive trends in the prevalence of tobacco smoking - compared to the GYTS 2011 data, it decreased by 1.7 times. It is mainly due to the reduction of smoking regular cigarettes, while the level of smoking new types of tobacco products increased. Thus, the proportion of adolescents smoked electronic cigarettes is 2 times higher compared to those smoked regular cigarettes (18.4 and 9.2 %, p < 0.05) regardless of gender. The part of respondents used smokeless tobacco products was 3.1 %. Every third child (both boys and girls) tried to smoke a water-pipe (28.4 %). The first smoking experience was most likely in the age group of 12-13 years. Every tenth adolescent tried to smoke before the age of 10 years that was 2.6 times less compared to the GYTS 2011 data and 3.1 times less compared to GYTS 2005 data. More than 13 % of smokers usually smoke in public open spaces such as shopping and entertainment centers, parks, cafes, clubs, etc. Only 2.8 % of respondents noted that they smoke at their homes (2.8 % (2017) and 12.2 % (2011), p < 0.05). Besides, the percentage of smokers purchased cigarettes in commercial network decreased (p < 0.01). The proportion of children who bought cigarettes in a store and were not refused purchase because of their age also decreased (from 55.7 to 6.7 %, p < 0.001). We consider that high level of children's awareness about negative tobacco smoking influence on human health is a positive factor for the formation of their health-saving behavior (GYTS 2011 - 72.6 %, GYTS 2017 - 85.6 %, p < 0.001). More than a half of respondents approve the ban of smoking in public open (51.2 %) and closed (70.4 %) spaces. Conclusions. The issue of tobacco smoking in modern adolescents requires the consolidation of efforts by teachers, school psychologists, public health specialists, and narcologists (in some cases) in three main areas: 1) prevention of smoking - it should be aimed at children who do not smoke, with the purpose of increasing their level of consciousness regarding their health, the formation of healthy life style skills and settings; 2) psychological assistance and treatment - it should be aimed at smokers with the purpose of helping them to quit smoking; 3) specialized treatment (narcological help) - it should be aimed at daily smokers with tobacco dependence in order to help them to get rid of this addiction and quit smoking.